Management of Vertebral Re-Fractures after Vertebroplasty in Osteoporotic Patients - Guarnieri, G. (Centauro S.r.l., 2009)
This study illustrates the usefulness of vertebral biopsy in osteoporotic patients previously treated with vertebroplasty (VP) who present at follow-up with a new fracture in a vertebral soma adjacent or distant from the collapsed vertebral body. Five hundred and fifty patients with osteoporotic vertebral collapse underwent a minimally invasive treatment with vertebroplasty (VP) for a total of980 vertebral bodies. The approach was unipedicular in 520 patients and bipedicular in 30. Only cases with unclear findings at MR or CT (23 patients) were scheduled for a vertebral biopsy before VP treatment. The biopsy results were positive for haematological disease in only eight patients. A vertebral biopsy was carried out during re-treatment with VP in all patients who presented a vertebral refracture in the three month follow-up at a site adjacent to or distant from the previously treated vertebra (21 patients). We have found new fractures of adjacent vertebrae in 15 patients and new fractures of distant vertebrae in 16 patients at three month follow-up examination. Five of the 31 cases (16%) of spinal refracture, where during vertebroplasty treatment a bone biopsy and a sternal medullary aspiration had been carried out, an anatomopathological response to multiple myeloma was responsible for the refracture. It is useful to perform a spinal bone biopsy during re-treatment of the vertebroplasty procedure to rule out multiple myeloma or other disease as the cause of the new collapse in patients with osteoporotic disease presenting a new vertebral fracture in an adjacent or distant site from the previously collapsed vertebral body.